Correlation between Parental Involvement and Student Discipline on the Quality of Education in High Schools in Central Java - Syamsu Rijal; Rukiyanto, Bernardus Agus; Siminto, Siminto (West Science Social and Humanities Studies, 2024)
This quantitative study investigates the influence of parental involvement and student discipline on the quality of education in high schools in Central Java. A sample of 110 participants, including students, parents, and teachers, provided responses on measures of parental involvement, student discipline, and perceptions of educational quality. Descriptive statistics, correlation analysis, and multiple regression analysis were employed to analyze the data. The results reveal significant positive correlations between parental involvement, student discipline, and educational quality. Moreover, both parental involvement and student discipline significantly predict perceptions of educational quality, highlighting their critical roles in shaping the overall educational experience. These findings underscore the importance of fostering collaborative partnerships between parents and schools, as well as implementing effective discipline practices, to enhance educational quality in high schools in Central Java.